The Importance of Audit Profession Development in Emerging Market Countries - Michas, Paul N (The Accounting Review, 2011)
ABSTRACT This study investigates the country-level development of the audit profession in emerging market countries and whether this development is associated with audit quality and auditor choice. I find that audit quality is higher for client companies located in countries with a more developed audit profession, after controlling for rule of law and investor protection. Specifically, Big 4 client companies' total and abnormal accruals are both lower, and earnings are more conservative in countries with stronger Audit Profession Development (APD). However, these results hold only for companies audited by a Big 4 auditor. Results also indicate that stronger APD is associated with a greater likelihood that a client company hires a Big 4 auditor. My findings contribute to the literature that explores differences in audit quality and determinants of auditor choice, the literature that explores cross-country differences in audit professions, and research on the characteristics and effectiveness of audit institutions in emerging market economies. Data Availability: Data are publicly available.